Every symmetric 3 x 3 global game of strategic complementarities is noise independent - Christian Basteck; Tijmen R. Daniëls (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
We prove that the global game selection in all 3 x 3 payoff-symmetric supermodular games is independent of the noise structure. As far as we know, all other proofs of noise independence of such games rely on the existence of a so-called monotone potential (MP) maximiser. Our result is more general, since some 3 x 3 symmetric supermodular games do not admit an MP maximiser. Moreover, a corollary is that noise independence does not imply the existence of an MP maximiser.
Keywords: C72; D82; 330; global games; noise independence; Nichtkooperatives Spiel; Theorie